2021
DOI: 10.1027/0269-8803/a000272
|View full text |Cite
|
Sign up to set email alerts
|

Feel Thine Own Self – Mood Congruency Evaluation of Emotional State Adjectives

Abstract: Abstract. The goal of the study was to explore event-related potential (ERP) differences during the processing of emotional adjectives that were evaluated as congruent or incongruent with the current mood. We hypothesized that the first effects of congruence evaluation would be evidenced during the earliest stages of semantic analysis. Sixty mood adjectives were presented separately for 1,000 ms each during two sessions of mood induction. After each presentation, participants evaluated to what extent the word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…Consistent with the associative network theory (Bower, 1981), the early studies suggested that moods may be represented as distinctive nodes in semantic memory, being linked to the nodes representing mood-congruent words. Yet, later research has revealed a less consistent pattern of results (e.g., Grzybowski et al, 2021; Pratt & Kelly, 2008; Sereno et al, 2015), rarely reporting mood-congruence effects hypothesised by Bower (1981). For instance, in a lexical decision task (LDT) study, Sereno et al (2015) found that both positive and negative moods facilitated response accuracy and latencies to positive and negative words of low and high frequency compared to the baseline conditions – neutral words and no mood induction.…”
Section: Introductionmentioning
confidence: 98%
“…Consistent with the associative network theory (Bower, 1981), the early studies suggested that moods may be represented as distinctive nodes in semantic memory, being linked to the nodes representing mood-congruent words. Yet, later research has revealed a less consistent pattern of results (e.g., Grzybowski et al, 2021; Pratt & Kelly, 2008; Sereno et al, 2015), rarely reporting mood-congruence effects hypothesised by Bower (1981). For instance, in a lexical decision task (LDT) study, Sereno et al (2015) found that both positive and negative moods facilitated response accuracy and latencies to positive and negative words of low and high frequency compared to the baseline conditions – neutral words and no mood induction.…”
Section: Introductionmentioning
confidence: 98%